Pengaruh Pengungkapan Sustainability Report pada Nilai Perusahaaan dengan Eco-efficiency sebagai Variabel Moderasi - Delarthana Sari, Ida Ayu Febryana; Budiasih, I Gusti Ayu Nyoman (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the effect of sustainability report disclosure on company value with eco-efficiency as a moderating variable. The sample in this study were companies included in the ASRRAT (Asia Sustainability Report Rating) ranking for the 2018-2023 period which were determined using the purposive sampling method and obtained 23 companies with 100 observation data. The data analysis technique used was Moderated Regression Analysis Sub-Group method. The results of the study indicate that sustainability report disclosure has a negative effect on company value and eco-efficiency is able to weaken the effect of sustainability report disclosure on company value.